Inhabitant’s attitude towards conserving large heritage areas: A case of Darmo heritage settlement-Surabaya, Indonesia - Erika Yuni Astuti (Fakultas Seni Rupa dan Desain ITB, 2019)
The problem in preserving a residential heritage area which is located in the city center is challenging. In this case study; Darmo Settlement has problems varying from high land taxation, building maintenance problem and a changing function due to economic pressure. A regulation to conserve the area has already been taken, but still the phenomenon of changing the old building into modern style has appeared. This research describes a recent heritage preservation process in a large area in Surabaya, Indonesia. The preservation of a large area is not a priority compared to a single building heritage preservation which has gained more support from Surabaya Municipality, even though both citizen and government perceived Darmo Settlement as a very important part of the city. Therefore, research to explore inhabitant awareness becomes important (Hague and Jenkins, 2005; Larkham, 2005; Townshend and Pendlebury, 1999; Rodwell, 2007) Darmo settlement is one of the oldest designed residential area in the eastern part of Indonesia and has been nominated by Surabaya Municipality as heritage area that needs to be preserved. For Surabaya citizen, Darmo settlement is perceived as an old residential area which has a special characteristic that cannot be found in the newly built parts of the city. To preserve a heritage area; it is important to keep its architectural appearance, natural environment, social factor, historical character, general environmental quality and morphology intact but adaptive (Townshend and Pendlebury, 1999 cited in Pendlebury, 2009, p.139). Hence, this paper focuses on Darmo residents’ attitude towards planning, and what are the inhabitants’ opinions and challenges about the area. An empirical research was conducted on the inhabitants both living in the building functioning as a house and as a commercial spot. It was found to be a challenge by senior inhabitants in financing the maintenance. There was also a need to adjust the buildings utility system and redesigning rooms in commercial buildings.